2022
DOI: 10.37105/iboa.134
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for new technologies of DMS-65 folding bridge construction

Abstract: The paper presents two new technologies for the construction of single-span road bridges using the DMS-65 folding bridge structure. These technologies have been successfully applied in practice and resulted in savings in bridge construction time and cost. The presented technological solutions allow to organize the construction of small bridges in conditions of limited space for the construction yard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The results revealed that the investigated Bailey bridges deflected more than the safe limit. Ostrowska & Chmielewski (2022) presented two new technologies for the construction of single-span road bridges using the DMS-65 folding bridge structure. The proposed technologies were applied in practice and resulted in savings in cost and time of bridge foldable construction.…”
Section: Andrzej Ambroziak Maciej Malinowski Mirosław Wałęgamentioning
confidence: 99%
“…The results revealed that the investigated Bailey bridges deflected more than the safe limit. Ostrowska & Chmielewski (2022) presented two new technologies for the construction of single-span road bridges using the DMS-65 folding bridge structure. The proposed technologies were applied in practice and resulted in savings in cost and time of bridge foldable construction.…”
Section: Andrzej Ambroziak Maciej Malinowski Mirosław Wałęgamentioning
confidence: 99%
“…barges of the required displacement) and handling (with adequate capacity) [11]. installation of structure on obstruction [14].…”
Section: Positioning Of Bays Delivered Fully Assembledmentioning
confidence: 99%
“…Subsequently, the assembly groups add the remaining elements of the girder, between the trusses they fasten the transverse beams, wind girders and other elements of the platform and equipment. In the last phase, the driveway elements of the structure are installed [14].…”
Section: Connecting Abutments For Crossing With a Short Assembly Sitementioning
confidence: 99%
See 1 more Smart Citation